2019
DOI: 10.1002/anie.201903290
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Plasmonic and Electrocatalytic Activation of Methanol Oxidation on Palladium–Silver Alloy Nanotubes

Abstract: Localized surface plasmon resonance (LSPR) excitation of noble metal nanoparticles has been shown to accelerate and drive photochemical reactions. Here, LSPR excitation is shown to enhance the electrocatalysis of a fuel‐cell‐relevant reaction. The electrocatalyst consists of PdxAg alloy nanotubes (NTs), which combine the catalytic activity of Pd toward the methanol oxidation reaction (MOR) and the visible‐light plasmonic response of Ag. The alloy electrocatalyst exhibits enhanced MOR activity under LSPR excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 42 publications
7
126
0
Order By: Relevance
“…67 LSPR excited hot electrons, on the other hand, may be transferred to the glassy carbon substrate electrode across the ohmic interface between Au and GC with the assistance of external voltage. 40,94 As the Tafel slopes depend on the strength of adsorption of the intermediate species, this would support our proposed mechanism in which hot holes can activate the M-O* bond at the surface during the OER, lowering its binding energy, which leads to a change in the rate limiting step. 32,35,82,84,85 It has been reported that the OER reaction mechanism and ratedetermining step cannot be unambiguously assigned simply according to the measured Tafel slope because surface intermediates, coverage, reaction pathways, and rate-determining steps may depend on the potential.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…67 LSPR excited hot electrons, on the other hand, may be transferred to the glassy carbon substrate electrode across the ohmic interface between Au and GC with the assistance of external voltage. 40,94 As the Tafel slopes depend on the strength of adsorption of the intermediate species, this would support our proposed mechanism in which hot holes can activate the M-O* bond at the surface during the OER, lowering its binding energy, which leads to a change in the rate limiting step. 32,35,82,84,85 It has been reported that the OER reaction mechanism and ratedetermining step cannot be unambiguously assigned simply according to the measured Tafel slope because surface intermediates, coverage, reaction pathways, and rate-determining steps may depend on the potential.…”
Section: Resultssupporting
confidence: 70%
“…While the enhancement of electrocatalytic activity can originate from both photothermal effects and LSPR-generated charge carriers, previous results have shown that photothermally induced temperature rise does not fully account for the enhanced electrocatalytic activity, and that non-thermal effect play a significant role. 94 However, from our current data, it is not possible to precisely quantify the relative contributions from LSPR-excited charge carriers and photothermal effects over the activities.…”
Section: View Article Onlinementioning
confidence: 82%
“…The same trend was observed in the following two cycles (Figure c). In addition, the peak intensity for each cycle is a little higher than that of the previous cycle, which reveals that the residual thermal and/or hot‐carrier effect created by LSPR excitation under visible‐light irradiation promotes the MOR activity . Furthermore, we also found that the electrocatalytic activity is linearly dependent on the power density of the irradiation source (Figure d).…”
Section: Resultsmentioning
confidence: 65%
“…Although some preliminary works have reported plasmon‐enhanced electrocatalytic oxidation reactions in fuel cells, the detailed understanding of the light‐improved mechanism of their increased activity is still insufficient. Moreover, it is still urgent to design an efficient plasmonic structure that can provide strong LSPR properties, especially in the visible‐light region, to further improve their electrooxidation activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, without the catalyst, the hydrogenation of 4-NP to 4-AP by NaBH4 is kinetically restricted due to kinetic barriers resulting from the large potential difference between 4-NP and BH4 -. 2 In recent years, noble metal nanoparticles (MNPs) have been discovered to exhibit high catalytic activity for selective reduction of 4-NP in the presence of NaBH4, such as Ag NPs, 3 Au NPs, 4 Pd NPs, 5 and Pt NPs. 6 Among these MNPs catalysts, Ag-based catalysts are distinctive (easy preparation, relatively low cost, less toxicity, high activity and good stability) and have been extensively utilized for 4-NP reduction.…”
Section: Introductionmentioning
confidence: 99%